Book review: Dag Hammarskjöld, the United Nations and the decolonisation of Africa - Passemiers, Lazlo (Southern Journal for Contemporary History, 2019)
Dag Hammarskjöld, the United Nations and the decolonisation of Africa, Henning Melber, London, Hurst & Company, 2019. 190 pp, ISBN: 9781787380042